p(x) = 2X^2 - 7x +1 then evaluate p(3) + p(1/2) + p(-2)
Answers
Answered by
1
(2*9 - 21 + 1) + (2*(1/4) - 7/2 + 1) + (8 + 14 + 1)
= (18 - 21 + 1) + (1/2 - 7/2 + 1) + 23
= - 2 - 2 + 23
= 19
= (18 - 21 + 1) + (1/2 - 7/2 + 1) + 23
= - 2 - 2 + 23
= 19
Answered by
2
Answer:
19
Step-by-step explanation:
p(3)= 2*9 - 21 + 1
p(1/2)= (2*(1/4) - 7/2 + 1)
p(-2)= (8 + 14 + 1)
now ,p(3) + p(1/2) + p(-2)=
= (18 - 21 + 1) + (1/2 - 7/2 + 1) + 23
= - 2 - 2 + 23
= 19
please mark my answer as brainlest. plzzzz
Similar questions